French romantic travel writing Chateaubriand to Nerval - Thompson, C. W. (Christopher W.) (Oxford : Oxford University Press, 2012)
A pioneering overview of the travel books produced by 14 French romantic writers - including Chateaubriand, Stael, Stendhal Hugo, Nerval, Sand, Merimee, Dumas, and Tristan - whose journeys ranged from Peru to Russia and from North America to North Africa and the Near East.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Travelers' writings, French -- History and criticism; French literature -- 19th century -- History and criticism; Romanticism -- France